The valuation-driven acquisition theory in mining M&As: are post-acquisition value write-downs indicative of target overvaluation? - Kapapilo, Angela (My University, 2021)
This research sought to find evidence of the “valuation-driven acquisition theory” and its possible relationship with post acquisition impairments in mining mergers and acquisitions (M&As) over between 2010 and 2012. The “valuation-driven acquisition theory” was defined by financial economics scholars such as Schleifer & Vishny (2003) and Rhodes-Kropf & Viswathan (2005) who studied market-and accounting-data derived valuations of companies involved in M&As and concluded that managers’ decisions to participate in M&A activities and M&A Target selection were driven by stock market misvaluations. The “valuation-driven acquisition theory” proposes that Bidders should limit their offer values to their own valuations to avoid potential post acquisition losses. Based on this, scholars such as Gu & Lev (2011) extended the “valuation-driven acquisition theory” by finding correlations between Bidder company valuations, Target company overpayment and post-acquisition impairments. Following examples from financial economics research, the Price-to-Book (PB) and Risk-adjusted Excess Returns (ER) valuation metrics for mining companies were derived using stock market data and accounting data so as to test M&A transactions for at least some of the propositions of the “valuation-driven acquisition theory”. Analysis of the PB and ER valuation metrics resulted in the following conclusions with respect to the “valuation-driven acquisition theory” propositions: (1) according to the ER metric analyses, Target and Bidder companies were overvalued relative to the industry; however the PB metric found the opposite to be true: Target and Bidder companies were undervalued relative to the industry valuations; (2) Both the ER and PB metrics found that Bidder companies had higher valuations than Target companies; and (3) there was no relationship between overall ER and PB industry valuations and M&A deal volumes. Based on these results, mining M&A activities show only mild support for the “valuation-driven acquisition theory”, and do not appear to be driven by trends in stock market misvaluations. It appears that average Target and Bidder company valuations differ from each other and from the overall average industry valuations, but the differences depend on the valuation metric used. Although based on a substantially small data set because annual impairments data was not available for all companies participating in M&A, comparison of valuation metrics to reported impairments and relative overpayment ratios resulted in the following conclusions: on average, Bidder companies with lower valuations reported more significant negative impairments and higher relative Target overpayment ratios. This group of Bidder companies and their respective Target companies appeared to have similar valuations. On average, Bidder companies with higher valuations reported positive impairments, had lower overpayment ratios and their Target companies had lower valuations than the Bidder companies. This analysis therefore found some correlation between valuations, target overpayments and reported impairments, and suggests that Bidder companies that bid for Targets with lower valuations report lower levels of impairments. In summary, the results of this research do not show strong evidence of the “valuation-driven acquisition theory” therefore it cannot be concluded that decisions by Mining Managers to participate in M&A activities and their Target selection strategies are driven by stock misvaluations. The main reason for this lies in the fact that the valuation methods used mimicked the methods prescribed in the financial economics literature which rely purely on stock market and accounting data for valuating industrial assets; however, the assets acquired during mining M&A activities are mineral resources which form the basis for the valuation of mining companies. The attractiveness of a mineral asset for selection as a potential M&A Target is based on factors such commodity prices, mineral resource characteristics, geographical location, development costs and/or operating costs. Only three valuation approaches are recognised by the mineral asset valuation codes, namely the income approach, cost approach and the market approach, and each of these are based on the underlying mineral resource. The conflicting results obtained by the valuation methods used in this research indicate that they are not suitable for determining the “misvaluation” of mining companies as the underlying mineral assets are not taken into consideration. Attempts to link the trends in the valuation metrics to impairments are therefore, by extension, futile. This research could be improved by conducting an analysis of mining acquisitions using mineral asset attractiveness factors to rate all mining acquisitions, study the history and details around each M&A transaction, and do a comparative analysis of impaired and non-impaired acquisitions to identify trends that cut across all impaired acquisitions. The results of such an analysis would be meaningful to the minerals industry, as the method would be directly related to factors that are actually relevant to the industry
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2021